Kepemilikan Institusional dan Perencanaan Pajak terhadap Manajemen Laba - Saraswati, Retno; Rachmawati, Nurul Aisyah (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2023)
One of the methods used to obtain maximum profit is to practice earnings management. The company's way of dealing with earnings management practices is by doing tax planning where the company minimizes the cost of paying taxes so that the profits obtained by the company increase. That way, the role and existence of institutional ownership to oversee fraudulent actions that exist within the company can suppress the occurrence of earnings management practices carried out by management. this study aims to determine and examine: (1) The effect of institutional ownership on earnings management in the Properties & Real Estate sector companies listed on the Indonesia Stock Exchange in 2018-2021, (2) The effect of tax planning on earnings management in companies Properties & Real Estate sector listed on the Indonesia Stock Exchange in 2018-2021. The data in this study uses secondary data obtained from the annual financial reports of companies in the Properties & Real Estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. This type of research is descriptive quantitative using a purposive sampling method with a sample of 40 companies which mere processed using the Stata 14.2 program. Based on the results of hypothesis testing, it was concluded that the independent variables of institutional ownership and tax planning had no significant effect on earnings management. However, simultaneously the independent variables of institutional ownership and tax planning have a significant effect on earnings management.